2001
DOI: 10.1038/35096585
|View full text |Cite
|
Sign up to set email alerts
|

The RNA component of telomerase is mutated in autosomal dominant dyskeratosis congenita

Abstract: Dyskeratosis congenita is a progressive bone-marrow failure syndrome that is characterized by abnormal skin pigmentation, leukoplakia and nail dystrophy. X-linked, autosomal recessive and autosomal dominant inheritance have been found in different pedigrees. The X-linked form of the disease is due to mutations in the gene DKC1 in band 2, sub-band 8 of the long arm of the X chromosome (ref. 3). The affected protein, dyskerin, is a nucleolar protein that is found associated with the H/ACA class of small nucleola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
650
1
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 881 publications
(678 citation statements)
references
References 28 publications
15
650
1
8
Order By: Relevance
“…Bone marrow insufficiency in a telomerasedeficient disease, DKC (Vulliamy et al, 2001), may be further evidence of that. Telomerase activity appears to be upregulated in response to cytokine-induced proliferation and cell cycle activation in primitive HSCs, and progressively downregulated in more matured subsets (Chiu et al, 1996) except for mitogenically activated lymphocytes (Hiyama et al, 1995) (Figure 1).…”
Section: Telomeres and Telomerase In Haematopoietic Stem Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…Bone marrow insufficiency in a telomerasedeficient disease, DKC (Vulliamy et al, 2001), may be further evidence of that. Telomerase activity appears to be upregulated in response to cytokine-induced proliferation and cell cycle activation in primitive HSCs, and progressively downregulated in more matured subsets (Chiu et al, 1996) except for mitogenically activated lymphocytes (Hiyama et al, 1995) (Figure 1).…”
Section: Telomeres and Telomerase In Haematopoietic Stem Cellsmentioning
confidence: 98%
“…Positional cloning identified the gene affected in many patients with X-linked DKC as the human homologue of yeast CBF5, termed DKC1, encoding a protein, dyskerin. The association of the telomerase complex with dyskerin suggested that the DKC phenotype may be the result of altered telomerase activity (Vulliamy et al, 2001). Then, the discovery of a 3 0 deletion in the gene encoding TERC in a single large family with autosomal dominant DKC confirmed the importance of telomerase deficiency as the aetiology for DKC and highlighted the importance of telomerase in maintaining cellular lifespan and replicative potential in human organs.…”
Section: Diseases Due To Lack Of Telomerase In Stem Cells: Dkc and Apmentioning
confidence: 99%
“…Mutations in dyskerin, which is involved in ribosomal RNA processing 3 and in the telomerase complex 4 , are responsible for the X-linked form of this disease 5 . Families with autosomal dominant inheritance of dyskeratosis congenita (AD-DC) have mutations in the gene encoding the RNA component of telomerase (TERC) 6 . These mutations seem to give rise to the disease through haploinsufficiency, through the absence of a 3â€Č end, impaired RNA accumulation or a catalytic defect 7 .…”
mentioning
confidence: 99%
“…In these families, affected individuals are heterozygous with respect to mutations in TERC. Three of the eight families and the mutations they carry were previously described 6 : family DCR063 (408C→G), family DCR082 (107-108GC→AG) and family DCR101 (3â€Č deletion, from nucleotide 378 onward). In two of the eight families, the index case presented with aplastic anemia: family DCR172 (72C→G) and family DCR174 (110-113 deletion GACT) 8 .…”
mentioning
confidence: 99%
“…Le lien entre DC et dysfonctionnement tĂ©lomĂ©rique s'est trouvĂ© renforcĂ© par l'identification de mutations dans d'autres composantes du complexe tĂ©lomĂ©rase dont la matrice ARN hTERC [14]. Des dĂ©lĂ©tions de hTERC sont responsables des formes autosomiques dominantes de DC.…”
Section: Formes Autosomiques Dominantesunclassified